Mitochondrial toxicity evaluation of traditional Chinese medicine injections with a dual in vitro approach - Shen, Yunfu; Guo, Kaiqiang; Ma, Aijun; Huang, Zhe; Du, Jingjing; Chen, Junhe; Lin, Qianyu; Wei, Chengming; Wang, Zi; Zhang, Fuming; Zhang, Juan; Lin, Wanjun; et al. (Frontiers in Pharmacology, 2022)
There are technical obstacles in the safety evaluation of traditional Chinese medicine (TCM) injections due to their complex chemical nature and the lack of rapid and accurate in vitro methods. Here, we established a dual in vitro mitochondrial toxicity approach combing the conventional “glucose/galactose” assay in HepG2 cells with the cytotoxic assay in mitochondrial respiration deficient cells. Using this dual in vitro approach, for the first time, we systematically assessed the mitochondrial toxicity of TCM injections. Four of the 35 TCM injections, including Xiyanping, Dengzhanhuasu, Shuanghuanglian, and Yinzhihuang, significantly reduced cellular ATP production in galactose medium in the first assay, and presented less cytotoxic in the respiration deficient cells in the second assay, indicating that they have mitochondrial toxicity. Furthermore, we identified scutellarin, rutin, phillyrin, and baicalin could be the potential mitochondrial toxic ingredients in the 4 TCM injections by combining molecular docking analysis with experimental validation. Collectively, the dual in vitro approach is worth applying to the safety evaluation of more TCM products, and mitochondrial toxic TCM injections and ingredients found in this study deserve more attention.